2004
DOI: 10.1212/wnl.62.10.1758
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid peroxidation in sera of ALS patients

Abstract: These data confirm the presence of increased oxidative stress and immune activation in ALS patients. HNE is also suggested as a possible biomarker of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(183 citation statements)
references
References 56 publications
7
170
1
5
Order By: Relevance
“…Oxidative stress is now widely believed to be involved in the pathogenesis of major age-related diseases such as neurodegenerative diseases [9][10][11][12][13][14][15][16], cancer [17,18] and a long list of several other human diseases such as ischemia-reperfusion injury [19], stroke [20,21], hypertension [3], diabetes [22], rheumatic diseases [23][24][25] and multiple sclerosis [26].…”
Section: Reactive Oxygen Species and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is now widely believed to be involved in the pathogenesis of major age-related diseases such as neurodegenerative diseases [9][10][11][12][13][14][15][16], cancer [17,18] and a long list of several other human diseases such as ischemia-reperfusion injury [19], stroke [20,21], hypertension [3], diabetes [22], rheumatic diseases [23][24][25] and multiple sclerosis [26].…”
Section: Reactive Oxygen Species and Oxidative Stressmentioning
confidence: 99%
“…On the other hand, CNS has high content of polyunsaturated fatty acids, which are very prone to oxidative damage and also contains large amounts of iron, which is involved in the formation of dangerous ROS like hydroxyl radical [12]. A large body of evidence exists on the involvement of oxidative stress in the pathogenesis of Alzheimer disease [9,10,12,13], Parkinson disease [11,16] and amyotrophic lateral sclerosis (ALS) [14].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Several studies have shown increased lipid peroxidation and DNA damage in transgenic mice expressing mutant SOD1 (an animal model for ALS) and in neural tissue or sera from ALS patients [55,56].…”
Section: Als and Lipid Peroxidationmentioning
confidence: 99%
“…Evidence for oxidative damage to proteins and lipids has been detected in serum, fibroblasts, and the central nervous system (CNS) of ALS patients as well as various organs in the G93A mutant SOD1 transgenic murine model of ALS (13)(14)(15)(16)(17)(18)(19)(20). A central regulator of cellular responses to oxidative stress is the NRF2 (NF-E2-related factor 2)/KEAP1 (Kelch-like ECH-associated protein 1) pathway.…”
mentioning
confidence: 99%